-6-11x=7x-12

Simple and best practice solution for -6-11x=7x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-11x=7x-12 equation:


Simplifying
-6 + -11x = 7x + -12

Reorder the terms:
-6 + -11x = -12 + 7x

Solving
-6 + -11x = -12 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-6 + -11x + -7x = -12 + 7x + -7x

Combine like terms: -11x + -7x = -18x
-6 + -18x = -12 + 7x + -7x

Combine like terms: 7x + -7x = 0
-6 + -18x = -12 + 0
-6 + -18x = -12

Add '6' to each side of the equation.
-6 + 6 + -18x = -12 + 6

Combine like terms: -6 + 6 = 0
0 + -18x = -12 + 6
-18x = -12 + 6

Combine like terms: -12 + 6 = -6
-18x = -6

Divide each side by '-18'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| 2x^2+56x-29=0 | | (4u+7)(6-u)=0 | | 7y=28y+6 | | 2z^2-17z+30= | | -9+5x=-14 | | -6=-3r | | (Y+5)+x=2.5y | | 70-3x=90-43x | | 3z^3*z= | | 9+3q=12+2q | | 11v-9v=4 | | 70-3x=90-11x | | (9x+12y)(9x-12y)= | | (Y-5)+x=2.5y | | 5(c-4)=6(c-5) | | log(x)-log(x+11)=-1 | | 3m-29=-44+8m | | 5(x+10)=7x-32 | | 4800000=2900000+1600x | | 3x^2+32x+20= | | -20-2x=-30 | | 6m-5=-23+9m | | -30=-84 | | 5y-4+y+30=8y+30-4y | | 3(3x+7)-7=18x+1-9x | | 2[3(X+y)-4(6x-5y)]= | | 6m-5=23+9m | | -(x-7y)-2(2y-5x)=0 | | 3(x+3)-2=3x+2 | | 3x(x^3+6)= | | 20x+25x=180 | | Y=-x+3y |

Equations solver categories